Factors impacting university-industry collaboration in European countries - Bojan Ćudić; Peter Alešnik; David Hazemali (Journal of Innovation and Entrepreneurship, 2022)
This paper aims to examine the links between university-industry collaboration (UIC) predictors (inputs) and the results of UIC cooperation (outputs). The focus of the research is UIC within the European Union member states and the Western Balkan countries. The analysis was conducted using the partial least squares structural equation modeling (PLS-SEM). This method enabled examining the links between variables that are not directly observable. The authors used data for the period of three years, 2015-2018. The results prove that countries investing in UIC predictors (inputs) have better UIC performance (outputs). Based on the statistical analysis, the authors identified the investments in knowledge, networking, and research and development (R&D), in general, as the most significant that impact UIC performance.
Keywords: 650; Europe; knowledge; Networking; PLS-SEM; R&D; University-industry collaboration